2005
DOI: 10.1207/s15327655jchn2201_5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Sensation Seeking, Compulsivity, and HIV Risk Behaviors in College Students

Abstract: The purpose of this descriptive and correlational study was to understand the role of sexual compulsivity, sensation seeking, and alcohol use as mediators of HIV risk behaviors among college students. College students (n = 256) completed an online survey in 2003. Instruments included the Sexual Compulsivity Scale (SCS), Sexual Sensation Seeking Scale (SSS), and the College Alcohol Problem Scale (CAPS). Men scored higher on the SSS and SCS than women. Women who belong to Greek organizations reported significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
70
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 28 publications
13
70
3
3
Order By: Relevance
“…They engage in new experiences and relationships, some of which are associated with increased sexual risks (Bailey et al 2008;Eisenberg et al 2012;Gullette and Lyons 2005). In recent years, some Spanish, European, and Latin American universities have adopted the Health Promoting University approach (Red Española de Universidades Saludables 2015; Tsouros et al 1998).…”
mentioning
confidence: 99%
“…They engage in new experiences and relationships, some of which are associated with increased sexual risks (Bailey et al 2008;Eisenberg et al 2012;Gullette and Lyons 2005). In recent years, some Spanish, European, and Latin American universities have adopted the Health Promoting University approach (Red Española de Universidades Saludables 2015; Tsouros et al 1998).…”
mentioning
confidence: 99%
“…We tested the ImpSS domain of the ZKPQ and found a significant correlation with sensation seeking, which is consistent with several previous studies. Some of these studies used a specific measure of sexual sensation seeking and found correlation coefficients ranging from .50 (sample of undergraduate students) (Gullette & Lyons, 2005) to .70 (community sample of same-gender sexually active men) (Kalichman & Rompa, 1995). Similar to our results, other studies have Arch Sex Behav investigated correlations with general sensation seeking and have found correlations coefficients ranging from .43 (sample of inner city men and women) to .57 (community sample of samegender sexually active men) (Kalichman & Rompa, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prior studies have included mixed samples and usually did not control for ethnic differences. Unfortunately, fewer studies have examined the relationship between SSS and risky sex among heterosexual youth and especially among those who are female (Gullette & Lyons, 2005;Spitalnick et al, 2007). More importantly, there is a dearth of studies which have examined the relationship between SSS and risky sex using prospective data (Kalichman et al, 1994(Kalichman et al, , 1996McCoul & Haslam, 2001).…”
mentioning
confidence: 99%